Reflections on the development of regional financing arrangements: Experience from Europe - Gong Cheng (Asian Development Bank Institute (ADBI), 2020)
This paper sheds light on the development of European Regional Financing Arrangements (RFAs) and the role of these financial backstops in resolving the recent euro area crisis. It documents a significant dual shift in the design of regional firewalls in Europe, from bilateral to multilateral financial assistance and from temporary rescue funds to the permanent European Stability Mechanism. This evolution epitomizes policy makers' deepened understanding of the root causes of the euro area crisis and the way forward to manage it. Based on the European experience, the paper aims to identify some potential lessons for other RFAs, especially for the Chiang Mai Initiative Multilateralization (CMIM) in East and Southeast Asia. The change in mentality about crisis resolution revealed the importance of having a deep understanding of the origin of region-specific shocks first, which will determine an RFA's mandate and operational scope. Within the remit of the mandate, which can evolve over time, an RFA develops and reshapes its lending tools and policies and finds the most suitable strategy to secure funding resources. The European experience could thus be useful to inspire the future evolution of the CMIM in the ASEAN+3 membership.
Keywords: F33; F34; F53; F55; G24; 330; regional financing arrangements; crisis prevention; crisis resolution; tool kit; governance; financial backstops; Asia; Europe